Traditional Chinese Medicine Shenmayizhi Decoction Ameliorates Memory And Cognitive Impairment Induced By Scopolamine Via Preventing Hippocampal Cholinergic Dysfunction In Rats - Wu, Qiong (Neuropsychiatr Dis Treat, 2019)
PURPOSE: Clinical trials have illustrated that Shenmayizhi decoction (SMYZ) could improve the cognitive functions in patients with dementia. However, the mechanism needs to be explored. METHODS: Fifty adult male rats (Wistar strain) were divided into five groups equally and randomly, including control, model, and SMYZ of low dose, medium dose and high dose. Rats in each group received a daily gavage of respective treatment. Rats in control and model group were administrated by the same volume of distilled water. Memory impairment was induced by intraperitoneal administration of scopolamine (0.7 mg/kg) for 5 continuous days. Four weeks later, Morris water maze (MWM) was performed to evaluate the spatial memory in all rats. Then, rats were sacrificed and the hippocampus was removed for further tests. Furthermore, Western blot analysis was employed to assess the levels of acetylcholine M1 receptor (M1), acetylcholine M2 receptor (M2), acetylcholinesterase (AChE) and cholineacetyltransferase (ChAT). AChE and ChAT activities were determined. RESULTS: The SMYZ decoction significantly improved behavioral performance of rats in high dose. The SMYZ decoction in three doses exhibited anti-acetylcholinesterase activity. In addition, a high dose of SMYZ promoted ChAT activity. Moreover, a high dose of SMYZ increased the level of ChAT and declined the level of AChE assessed by Western blotting. Besides, an increased level of M1 receptor was found after treatment. CONCLUSION: Shenmayizhi decoction could mitigate scopolamine-induced cognitive deficits through the preventative effect on cholinergic system dysfunction.